The effect of incubation temperature on early malformation, regionalisation and meristic characters of the vertebral column in farmed Chinook salmon (Oncorhynchus tshawytscha) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Science at Massey University, Manawatū, Palmerston North, New Zealand - De Clercq, Adelbert (Massey University, 2018)
Skeletal deformities are a recurrent problem in farmed Chinook salmon which limit production and have animal welfare impacts. Skeletal deformities of a variety of types are recognised especially when the external phenotype of the animal is affected. These types are well described in juvenile and adult stages of the production cycle. Which skeletal malformations affect early life stages in salmonids is less well known. Temperature is commonly manipulated in fish farming husbandry. High rearing temperatures are related to higher growth rates and in Atlantic salmon, elevated temperature has been inferred as a potential risk factor for skeletal deformities. In this thesis, malformations of the vertebral column in post-hatch to first feed life stages (500-900 degreedays) were studied in farmed Chinook salmon (Oncorhynchus tshawytscha) in New Zealand. Fish were reared at a constant 4°C, 8°C and 12°C, from fertilisation to juvenile stages. The effects of rearing fish at these temperatures on malformations of the vertebral column were studied in specimens whole-mount stained for cartilage and mineralised bone, and in histological sections. The external phenotype of post-hatch stages could be linked to internal skeletal malformations such as notochord malformations, chordacentra fusions and malformations of the associated elements. In all temperature groups, externally normal specimens could have internal malformations, predominantly fused chordacentra. Conversely, externally malformed fish usually displayed internal malformations. Specimens raised at 8°C had fewest malformations, followed by specimens of the 12°C group. Specimens raised at 4°C had the highest number of malformations. This study indicates that 8°C is the best incubation temperature of those tested. In addition, the effects of rearing temperature on morphological variation of skeletal elements such as vertebrae, vestigial ribs and vestigial elements in the caudal fin were studied. Six vertebral column regions were identified. The defining characters of each of these regions remained independent of the rearing temperature. Still, the postcranial, transitional and ural regions showed temperature sensitive meristic variation of the vertebrae, vestigial ribs, arches, epurals and uroneurals. Meristic variation can foreshadow skeletal malformations that emerge late in life and thus be significant for the early diagnosis of vertebral deformities.
Chapter 3 was published as: De Clercq, A., Perrott, M.R., Davie, P.S., Preece, M.A., Huysseune, A., & Witten, P.E. (2017). The external phenotype–skeleton link in post‐hatch farmed Chinook salmon (Oncorhynchus tshawytscha). Journal of Fish Diseases, 41(3): 511–527. https://doi-org.ezproxy.massey.ac.nz/10.1111/jfd.12753 Chapter 4 was published as: De Clercq, A., Perrott, M.R., Davie, P.S., Preece, M.A., Wybourne, B., Ruff, N., Huysseune, A., & Witten, P.E. (2017). Vertebral column regionalisation in Chinook salmon, Oncorhynchus tshawytscha. Journal of Anatomy, 231(4): 500--514. https://doi-org.ezproxy.massey.ac.nz/10.1111/joa.12655 Chapter 5 was published as: De Clercq, A., Perrott, M.R., Davie, P.S., Preece, M.A., Owen, M.A.G., Huysseune, A., & Witten, P.E. (2018). Temperature sensitive regions of the Chinook salmon vertebral column: Vestiges and meristic variation. Journal of Morphology 279(9): 1301-1311. https://doi-org.ezproxy.massey.ac.nz/10.1002/jmor.20871
Keywords: Chinook salmon; Anatomy; Development; Effect of habitat modification on; Musculoskeletal system; Abnormalities; Salmon farming; New Zealand; Aquaculture